IMPLEMENTASI PENDIDIKAN KARAKTER DAN FUNGSI PSIKOLOGIS BAGI SISWA SMK - Surniaty Chalid (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT The development of each individual character as a teenager influenced by heredity (nature) and environmental factors (nurture). According to developmental psychologist, every human being has the inherent potential to be manisfasted after she was born, including the potential associated with the character or virtue . Socialization and education of children with regard to the good values ​​ in the family, school , and the wider environment, is very important in shaping a child's character. The purpose of writing to help teachers understand the character of the students closer , who was still a teenager seen from the perspective of psychological, social, and cultural . In addition to being a preventive measure and interventif  for teachers in mentally preparing graduates as well aims to establish the characteristics of vocational students, so expect graduates to be personal beings , superior and skilled and skillful, so it is not just  and competent in the koqnitif but once proficient in intelligence affective, intelligence and wit liver flavor. Character education is used as a character value cropping systems, including the components of knowledge, awareness or volition , and actions to implement the value, both to the Almighty God, ourselves, others, the environment, or nationality to become a perfect human being. Character education in schools, all of the components (stakeholders ) should be involved , including educational components themselves, ie the content of the curriculum, learning and assessment, the quality of relationships, handling or management of subjects, school management, the implementation of the activities or co-curricular activities, empowerment infrastructure, financing, and work ethic of all citizens and the school environment. Kata Kunci : SMK, Pendidikan Karakter dan usia remaja.